Rethinking Islamic political thought: Wilāyat al-Faqīh and the caliphate through Ibn Qayyim's theory of legal change - Aan Afandi; Dykasakti Azhar Nytotama (Mishkat: Journal of Theology and Civilization, 2026)
Studies on Wilāyat al-Faqīh have primarily emphasized its theological and constitutional dimensions, while comparative analyses with Taqiyuddin An-Nabhani's concept of the Caliphate through Ibn Qayyim al-Jawziyyah's theory of legal change remain limited. This study aims to examine Ayatollah Khomeini's concept of Wilāyat al-Faqīh, compare it with An-Nabhani's concept of the Caliphate, and interpret both through Ibn Qayyim al-Jawziyyah's theory of legal change. This qualitative study employed a library research approach using descriptive-comparative analysis of primary and secondary sources. The findings reveal that Wilāyat al-Faqīh represents a reconstruction of Shiʿi political thought grounded in the doctrine of Imāmah during the Occultation of the Imam, whereas An-Nabhani's concept of the Caliphate derives its political legitimacy from the bayʿah of the Muslim community. Viewed through Ibn Qayyim al-Jawziyyah's perspective, both represent forms of political ijtihād shaped by historical and social contexts. Consequently, this study contributes to the scholarship on Islamic political thought by offering a contextual comparative framework for understanding the diversity of Islamic models of governance. Abstrak Kajian mengenai Wilāyat al-Faqīh umumnya berfokus pada dimensi teologis dan ketatanegaraan, sedangkan analisis komparatif dengan konsep khilafah Taqiyuddin An-Nabhani melalui perspektif teori perubahan hukum Ibnu Qayyim al-Jauziyah masih relatif terbatas. Penelitian ini bertujuan menganalisis konsep Wilāyat al-Faqīh menurut Ayatollah Khomeini, membandingkannya dengan konsep khilafah Taqiyuddin An-Nabhani, serta menginterpretasikan keduanya melalui perspektif teori perubahan hukum Ibnu Qayyim al-Jauziyah. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan serta analisis deskriptif-komparatif terhadap sumber primer dan sekunder. Hasil penelitian menunjukkan bahwa Wilāyat al-Faqīh merupakan rekonstruksi politik Syiah yang berakar pada doktrin imamah pada masa kegaiban Imam, sedangkan konsep khilafah An-Nabhani memperoleh legitimasi politik melalui bai'at umat. Ditinjau dari perspektif Ibnu Qayyim al-Jauziyah, kedua konsep tersebut merupakan bentuk ijtihad politik yang berkembang sesuai dengan konteks sejarah dan sosial. Oleh karena itu, penelitian ini berkontribusi memperkaya kajian politik Islam melalui kerangka analisis komparatif yang kontekstual.